2015
DOI: 10.1038/srep18678
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectrum of KRAS, NRAS, BRAF and PIK3CA mutations in Chinese colorectal cancer patients: analysis of 1,110 cases

Abstract: Mutations in genes such as KRAS, NRAS, BRAF and PIK3CA have become an important part of colorectal carcinoma evaluation. The aim of this study was to screen for mutations in these genes in Chinese patients with colorectal cancer (CRC) and to explore their correlations with certain clinicopathological parameters. We tested mutations in the KRAS (exons 2, 3 and 4), NRAS (exons 2, 3 and 4), PIK3CA (exon 20) and BRAF (exon 15) genes using reverse transcriptase-polymerase chain reaction (RT-PCR) and Sanger sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
92
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 47 publications
21
92
3
5
Order By: Relevance
“…Existing data have remained inconclusive. Although better prognosis was reported in breast cancer with PIK3CA mutation, it was an unfavorable prognostic factor for colorectal cancer and NSCLC 14, 24, 25. The coexistence of PIK3CA and other driver genes may affect the analysis of PIK3CA as a prognostic marker.…”
Section: Discussionmentioning
confidence: 97%
“…Existing data have remained inconclusive. Although better prognosis was reported in breast cancer with PIK3CA mutation, it was an unfavorable prognostic factor for colorectal cancer and NSCLC 14, 24, 25. The coexistence of PIK3CA and other driver genes may affect the analysis of PIK3CA as a prognostic marker.…”
Section: Discussionmentioning
confidence: 97%
“…KRAS mutation prevalence in cholangiocarcinoma ranged from 16% to 38%. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Frequency Of Ras Mutation In Gastrointestinal Cancermentioning
confidence: 99%
“…Zhang et al have reported differences in the genetic profiles of KRAS, NRAS, PIK3CA, and BRAF at mutation hotspots between CRC patients from China and those from Western countries. The rate of these mutations in Arab patients with CRC is not well defined (9). The evaluations of the rates of these mutations in Arab population with CRC have been limited to few mutations including KRAS and BRAF (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Gene mutation and defective cell regulation are important processes in the development of CRC (6). Accumulation of these mutations, including mutations in KRAS, NRAS, BRAF and PIK3CA, activate multiple signaling pathways, such as RAS-RAF-MAPK and PI3K-PTEN-AKT, that play a major role in regulating cell proliferation, angiogenesis, cell motility and apoptosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%